Dot the Ladybug : the missing dot [book with audioplayer] - George, K. (Kallie), 1983- (I can read! My first shared reading, 2024)
Spot the dog's snack is missing its dot, so Dot the Ladybug looks for clues, in this My First I Can Read story that is perfect for readers who love simple wordplay and adorable illustrations.